Synergetic effect of lytic polysaccharide monooxygenase from Thermobifida fusca on saccharification of agrowastes. (June 2023) - Park, Hyun June; Gwon, Seung Yeon; Lee, Jeongmi; Koo, Na Kyeong; Min, Kyoungseon
Graphical abstract: Highlights: TfLPMO functioned on various cellulosic and hemicellulosic substrates. TfLPMO with cellulase showed a synergistic effect on saccharification of agrowaste. TfLPMO boosted rice straw-derived reducing sugars production by 19.2% TfLPMO boosted corncob-derived reducing sugars by 14.1% Abstract: Saccharification is one of the most noteworthy processes in biomass-based biorefineries. In particular, the lytic polysaccharide monooxygenase has recently emerged as an oxidative cleavage-recalcitrant polysaccharide; however, there is insufficient information regarding its application to actual biomass. Accordingly, this study focused optimizing the recombinant expression level of a bacterial lytic polysaccharide monooxygenase from Thermobifida fusca (TfLPMO), which was characterized as a cellulolytic enzyme. Finally, the synergistic effect of the lytic polysaccharide monooxygenase and a commercial cellulase cocktail on the saccharification of agrowaste was investigated. TfLPMO functioned on various cellulosic and hemicellulosic substrates, and the combination of TfLPMO with cellulase exhibited a synergistic effect on the saccharification of agrowastes, resulting in a 19.2% and 14.1% increase in reducing sugars from rice straw and corncob, respectively. The results discussed herein can lead to an in-depth understanding of enzymatic saccharification and suggest viable options for valorizing agrowastes as renewable feedstocks in biorefineries.